1987
DOI: 10.1007/bf01663472
|View full text |Cite
|
Sign up to set email alerts
|

Quantum analogues of the Bell inequalities. The case of two spatially separated domains

Abstract: THE CASE OF UDC 519.2 One investigates inequalities for the probabilities and mathematical expectations which follow from the postulates of the local quantum theory. It turns out that the relation between the quantum and the classical correlation matrices is expressed in terms of Grothendieck's known constant. It-is also shown that the extremal quantum correlations characterize the Clifford algebra (i.e., canonical anticommutative relations).The Bell inequalities are inequalities for probabilities that are val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
351
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(360 citation statements)
references
References 8 publications
9
351
0
Order By: Relevance
“…In order to prove Tsirelson's bound, we will now exhibit an optimal solution for both the primal and dual problem and then show that the value of the primal problem equals the value of the dual problem. The optimal solution is well known [17,15,11]. Alternatively, we could easily guess the optimal solution based on numerical optimization by a small program for Matlab 1 and the package SeDuMi [14] for semidefinite programming.…”
Section: Tsirelson's Boundmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to prove Tsirelson's bound, we will now exhibit an optimal solution for both the primal and dual problem and then show that the value of the primal problem equals the value of the dual problem. The optimal solution is well known [17,15,11]. Alternatively, we could easily guess the optimal solution based on numerical optimization by a small program for Matlab 1 and the package SeDuMi [14] for semidefinite programming.…”
Section: Tsirelson's Boundmentioning
confidence: 99%
“…Many thanks to Boris Tsirelson for sending me a copy of [17] and [15], to Oded Regev for pointing me to [2] and for introducing me to the concept of approximation algorithms such as [9], to Serge…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…In fact, it is true that jtrðB CHSH rÞj% 2 ffiffi ffi 2 p for all observables A 1 , A 2 , B 1 and B 2 , and all states r. Such a bound on the maximum entangled value of a Bell inequality is termed a Tsirelson bound (Cirel'son 1980). Although we do not yet know how to calculate the best such bound for an arbitrary Bell inequality, a number of ad hoc techniques have been developed (Cirel'son 1980;Tsirelson 1987;Buhrman & Massar 2004;Cleve et al 2004;Masanes 2005;Navascués et al 2007Navascués et al , 2008Doherty et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…By measuring the shared entangled state the provers can generate correlations which they can use to deceive the verifier. Tsirelson [25,23] has shown that even quantum mechanics limits the strength of such correlations. Consequently, Popescu and Roehrlich [16,17,18] have raised the question why nature imposes such limits.…”
Section: Introductionmentioning
confidence: 99%